1977
DOI: 10.1111/j.1399-6576.1977.tb01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow in the Rabbit Tracheal Mucosa under Normal Conditions and under the Influence of Tracheal Intubation

Abstract: Isotope labelled microspheres were used to study the capillary blood perfusion of the rabbit tracheal mucosa. Under resting conditions the perfusion was about 0.3 ml/min - g (i.e. about 60% of the relative cerebral blood flow). Irritation of the tracheal mucosa by an endotracheal tube caused a steep rise in blood flow, tenfold or more. This was probably due to relaxation of the arterioles caused by a release of histamine-like substances. When an endotracheal tube is equipped with a small cuff (small resting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0
10

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(74 citation statements)
references
References 26 publications
1
63
0
10
Order By: Relevance
“…Airway epithelium is now used as a well-established model of chemical carcinogenesis (Becci et al, 1978a, Nettesheim et al, 1981. Airway epithelium is also used in studies of the biology of wound repair (Gordon and Lane, 1980;Nordin et al, 1977;Schmidt et al, 1979) and the response to inhaled irritants such as sulfur dioxide (Lamb and Reid, 1968;Asmundson et al, 1973;Clark et al, 19801, ozone (Penha and Werthamer, 1974;Boatman et al, 1974;Schwartz et al, 1976;Mellick et al, 1977;Castleman et al, 1977), tobacco smoke (Frasca et al, 1968b;Hayashi et al, 19781, and marijuana smoke (Hayashi et al, 1979). Most of these experiments use laboratory rodents.…”
mentioning
confidence: 99%
“…Airway epithelium is now used as a well-established model of chemical carcinogenesis (Becci et al, 1978a, Nettesheim et al, 1981. Airway epithelium is also used in studies of the biology of wound repair (Gordon and Lane, 1980;Nordin et al, 1977;Schmidt et al, 1979) and the response to inhaled irritants such as sulfur dioxide (Lamb and Reid, 1968;Asmundson et al, 1973;Clark et al, 19801, ozone (Penha and Werthamer, 1974;Boatman et al, 1974;Schwartz et al, 1976;Mellick et al, 1977;Castleman et al, 1977), tobacco smoke (Frasca et al, 1968b;Hayashi et al, 19781, and marijuana smoke (Hayashi et al, 1979). Most of these experiments use laboratory rodents.…”
mentioning
confidence: 99%
“…Earlier studies o f the blood flow in other organs have shown that even slight injuries to the organ may give a considerable rise o f the blood flow (Nordin et al, 1977;Lindblom et al, 1978). In the present investigation we were unable to demonstrate that infectious diseases o f the middle ear or surgery o f the middle or inner ear caused any changes o f the blood flow within the cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of POST is attributed to trauma, local irritation and inflammation of the airway mucosa during tracheal intubation [13][14][15] . This tissue damage results in the release of prostaglandins which cause inflammation and pain 20,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postoperative sore throat (POST) after tracheal intubation varies from 6.6 to 90% [7][8][9][10][11][12] . The pathogenesis of POST is attributed to traumatisation, local irritation and inflammation of the airway mucosa during tracheal intubation [13][14][15] . Numerous non-pharmacological and pharmacological measures aimed at attenuating POST have been investigated with varying success.…”
Section: Introductionmentioning
confidence: 99%